Evaluation of patients with spontaneous pneumomediastinum diagnosis in the emergency department - Goktekin, Mehmet Cagri (Cukurova Univ, Fac Medicine, 2019)
Purpose: The aim of this study was to retrospectively evaluate the patients with spontaneous pneumomediastinum (SPM) diagnosis in the emergency department Materials and Methods: Data of the patients diagnosed by the SPM in the emergency department between January 2010 and December 2017 was analyzed in our study planned as monocenter and retrospective. The patients diagnosed by secondary pneumomediastinum (traumatic, invasive operation or postoperative, infections) were excluded from the study. Results: Mean age of 31 patients diagnosed by the SPM was 48.35 +/- 20.80/years and 74% of them (n=23) were male. The SPM development was significantly more in the males. The most accompanying disease was the chronic obstructive respiratory disease. The most frequent symptom was the shortness of breath. 61.29% of the patients were the smoker. The most disease triggering factor was the physical effort at the rate of 32%. It was determined that 35.5% of the patients were applied to the emergency department in the autumn and 32.3% of them in the spring. Hamman's sign existed in 25.8% of the patients. While the hospitalization period was mean 5.61 +/- 5.57, no mortality was seen in the emergency department. Conclusion: The SPM should be considered as a differential diagnosis in the patients applied to the emergency department with acute chest pain and shortness of breath.
Keywords: Emergency department; dyspnea; spontaneous pneumomediastinum